1967
DOI: 10.1037/h0025189
|View full text |Cite
|
Sign up to set email alerts
|

Concept-shift and discrimination-reversal learning in humans.

Abstract: Current studies of concept-shift and discrimination-reversal learning in humans are reviewed under 6 headings: (a) partial reinforcement during extradimensional shift, (b) number of response choices, (c) Age X Type of Shift, (d) intelligence, (e) degree of original training, and (f) verbal, perceptual, and attentional factors. In addition, several theoretical accounts of the shift process are considered and an effort is made to evaluate each of them in terms of the evidence presented in the review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
1

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 162 publications
9
66
1
Order By: Relevance
“…The performance of subjects trained on a high-dominant dimension (form) and maintained on that same dimension during the shift (10 group) did not differ reliably from the performance of subjects trained on a lowdominant (position) and shifted to a high-dominant dimension (ED group) . This finding and the significant influence of dimensional dominance in initial training are consistent with Wolff's (1967) suggestion that almost all subjects, regardless of age, dimcnsionalize stimuli in discrimination tasks. Seitz and Weir (1971) have proposed that older children and adults should be mixed dimensional responders and not have a dominant dimension.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The performance of subjects trained on a high-dominant dimension (form) and maintained on that same dimension during the shift (10 group) did not differ reliably from the performance of subjects trained on a lowdominant (position) and shifted to a high-dominant dimension (ED group) . This finding and the significant influence of dimensional dominance in initial training are consistent with Wolff's (1967) suggestion that almost all subjects, regardless of age, dimcnsionalize stimuli in discrimination tasks. Seitz and Weir (1971) have proposed that older children and adults should be mixed dimensional responders and not have a dominant dimension.…”
Section: Discussionsupporting
confidence: 79%
“…However, there was a substantial effect due to dimensional dominance [F(l ,40) = 168.47 , P < .001] which accounted for 80% of the total variance. Consistent with similar studies using children as subjects (Wolff, 1967), the form-relevant group (mean = 1.88) made fewer errors than the position-relevant group (mean = 7.00).…”
Section: Initial Trainingsupporting
confidence: 77%
“…What is of interest is that the EDS group solved the shift problem faster than did the IDS group, 9.04 vs 14.33 blocks to solution (t = 2.46, df = 46, P < .02). This is the opposite of what is usually found with college·age Ss (see Wolff, 1967, for a review of this literature). Table 1 shows summary statistics for some characteristics of hypothesis sampling for various groups of Ss.…”
Section: Resultscontrasting
confidence: 42%
“…Whether the learning of an extradimensional shift (EDS) is similarly facilitated by this variable is open to question. Considering this matter in a recent article, Wolff (1967) tentatively concluded that the exact effect of overtraining on EDS may ultimately depend on both individual difference variables and procedural variations in the administration of the shift itself. More specifically, he hypothesized that the magnitude of overtraining facilitation is an inverse function of both subject age and the degree of stimulus change from original to transfer learning, Supporting this hypothesis are the following facts.…”
mentioning
confidence: 99%
“…(See Wolff, 1967, for a review of pertinent studies.) Whether the learning of an extradimensional shift (EDS) is similarly facilitated by this variable is open to question.…”
mentioning
confidence: 99%